Elitistic interpretation of future top-level sport - Bonacin, D. (Acta Kinesiologica, 2009)
The purpose of this article was review of deliberation connected with future sport elitism. Approach was generic, i.e. with elaboration of elitism genesis as phenomenon. It was consulted numerous literature, but with unsatisfied accordance and without unique aspect of it, so discussion was oriented forward to only one remaining direction - management. It was concluded that in sport there exists only one real elite and that is manager`s elite, and that it is the only one real chance for sport development in the future. Value of article can be recognised in open-minded access and accentuation of management role that is expected to be only sport elite, but exclusively according to abilities of salvation of actual and strategic tasks.